UZBEKISTAN VILLAGES IN THE YEARS AFTER THE SECOND WORLD WAR: SOCIOECONOMIC PROBLEMS. 1945-1960 YEARS, AS AN EXAMPLE OF FERGANA REGION - Yusupov Jo‘rabek Xasanboyevich (Western European Studies, 2023)
In the article, the villages of Uzbekistan in the years after the Second World War: socio-economic problems of 1945-1960, as an example of Fergana region, were considered and opinions were given.
Keywords: The national economy of Uzbekistan; relations; ideological Soviet system